Effect of Routine Gastric Residual Aspiration on the Preterm Infant Fecal Microbiome - Lenfestey, Mary W.; Li, Nan; Gauthier, Josee; Winglee, Kathryn; Fodor, Anthony; Zeng, Ke; Jobin, Christian; Neu, Josef; Parker, Leslie A. (American Journal of Perinatology, 2022)
Objective Enteral feeding tubes are used in neonatal intensive care units (NICUs) to assess feeding tolerance by utilizing preprandial gastric residual aspiration. This study evaluates the effect of gastric residual aspiration on the preterm infant fecal microbiome and gastrointestinal inflammation.Study Design Fifty-one very low birth weight (VLBW) infants (≤32 weeks' gestational age and ≤1,250 g) enrolled in a larger single-center randomized controlled trial evaluating the effects of routine and nonroutine gastric residual aspiration were selected for further analysis. Of those infants, 30 had microbiome analysis performed on stools collected at 6 weeks by sequencing the bacterial V1 to V3 variable regions of the genes encoding for 16S rRNA. In an additional 21 infants, stool samples collected at 3 and 6 weeks were analyzed for intestinal inflammation using a cytokine multiplex panel.Results Microbial communities between groups were not distinct from each other and there was no difference in intestinal inflammation between groups. Analyses using gene expression packages DESeq2 and edgeR produced statistically significant differences in several taxa, possibly indicating a more commensal intestinal microbiome in infants not undergoing gastric residual aspiration.Conclusion Omission of routine gastric residual aspiration was not associated with intestinal dysbiosis or inflammation, providing additional evidence that monitors preprandial gastric residuals is unnecessary.Key Points
Keywords: neonate; gastric residual; gastric aspiration; microbiome